Early life conditions, adverse life events, and chewing ability at middle and later adulthood - Listl, Stefan; Watt, Richard; Tsakos, Georgios (American journal of public health, 2014)
Objectives. We sought to determine the extent to which early life conditions and adverse life events impact chewing ability in middle and later adulthood.Methods. Secondary analyses were conducted based on data from waves 2 and 3 of the Survey of Health, Ageing, and Retirement in Europe (SHARE), collected in the years 2006 to 2009 and encompassing information on current chewing ability and the life history of persons aged 50 years or older from 13 European countries. Logistic regression models were estimated with sequential inclusion of explanatory variables representing living conditions in childhood and adverse life events.Results. After controlling for current determinants of chewing ability at age 50 years or older, certain childhood and later life course socioeconomic, behavioral, and cognitive factors became evident as correlates of chewing ability at age 50 years or older. Specifically, childhood financial hardship was identified as an early life predictor of chewing ability at age 50 years or older (odds ratio = 1.58; 95% confidence interval = 1.22, 2.06).Conclusions. Findings suggest a potential enduring impact of early life conditions and adverse life events on oral health in middle and later adulthood and are relevant for public health decision-makers who design strategies for optimal oral health.